2015
DOI: 10.1530/jme-15-0076
|View full text |Cite
|
Sign up to set email alerts
|

CRTC2 and Nedd4 ligase involvement in FSH and TGFβ1 upregulation of connexin43 gap junction

Abstract: The major mission of the ovarian follicle is the timely production of the mature fertilizable oocyte, and this is achieved by gonadotropin-regulated, gap junction-mediated cell-cell communication between the oocyte and surrounding nurturing granulosa cells. We have demonstrated that FSH and transforming growth factor beta 1 (TGFb1) stimulate Gja1 gene-encoded connexin43 (Cx43) gap junction formation/function in rat ovarian granulosa cells is important for their induction of steroidogenesis; additionally, cAMP-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 59 publications
0
11
0
Order By: Relevance
“…TGF-β factors have been reported to facilitate FSH functions in gap junction formation and steroidogenesis by enhancing the activity of CREB-regulated transcription coactivator (CRTC2, also known as TORC2) [ 121 , 122 ]. TORC2 can sense both cAMP/PKA and calcium signaling induced by FSH [ 122 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…TGF-β factors have been reported to facilitate FSH functions in gap junction formation and steroidogenesis by enhancing the activity of CREB-regulated transcription coactivator (CRTC2, also known as TORC2) [ 121 , 122 ]. TORC2 can sense both cAMP/PKA and calcium signaling induced by FSH [ 122 ].…”
Section: Introductionmentioning
confidence: 99%
“…FSH’s stimulation of TORC2 may not be a lasting effect. A later rise as well as translocation of TORC2 requires synergia of TFGβ1 [ 121 , 122 ]. And in this process, rather than PKA, calcineurin seems to matter, which requires further study to figure out the molecular mechanism underlying TGF-β affected calcineurin activities.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, we observed that transcripts abundance of CX43 and FOXO1 increased with age in the GCs of untreated animals. These genes encode key regulators of GC function, proliferation, and survival, and their expression was shown to be regulated by FSH in different species (Ackert, Gittens, O'Brien, Eppig, & Kidder, 2001;Cunningham, Zhu, Unterman, & Hammond, 2003;Fang et al, 2015;Nuttinck et al, 2000;Santiquet, Robert, & Richard, 2013;Shen et al, 2014;Ting & Zelinski, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…While classic lysine-based motifs may not be responsible for direct ubiquitin binding, more recent studies have shown that proline-rich regions of the Cx43 C-terminus (xPPxY) bind to ubiquitin ligase. A number of ubiquitin ligases have also been associated with direct binding, internalization, and degradation of Cx43 (e.g., Trim21 [ 291 ], WWP1 [ 292 ], SMURF2 [ 293 ], and NEDD4 [ 287 , 288 , 289 , 294 ]). NEDD4 also has been directly associated with loss of Cx43 at the plasma membrane in experimental models [ 287 ].…”
Section: Post-translational Regulation Of Connexinsmentioning
confidence: 99%